ANALISIS MAJAS PERBANDINGAN DALAM PUISI “ROCK CLIMBING” KARYA JUNIARSO RIDWAN - Fatimah Insanul Hakim; Riana Dwi Lestari; Ika Mustika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The use of figure of speech in poetry is very important, because poetry is a work that contains beauty. Language style in poetry makes language in poetry different from literature in general. This research was conducted with the aim of knowing what comparative figures are contained in one of Juniarso Ridwan's poems entitled "Rock Climbing". This research was conducted using descriptive qualitative methods and then examined using a stylistic study. Where the process of studying this poetry uses text analysis techniques by: reading poetry, understanding every meaning in the poem, finding and interpreting words that contain figure of speech, connecting with types of figure of speech and describing it. From the research that has been done, it is concluded that in the poem entitled "Rock Climbing" by Juniarso Ridwan, almost every line contains comparative figures, including personification, synesthesia, symbolic and simile figures.